Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(4^2x+4^2.10=160\)
\(4^2\left(x+10\right)=160\)
\(16\left(x+10\right)=160\)
\(x+10=10\)
\(x=0\)
vay \(x=0\)
\(\left(12x-4^3\right).8^3=4.8^4\)
\(\left(12x-4^3\right).8^3-4.8^4=0\)
\(\left(12x-64\right).8^3-4.8^4=0\)
\(8^3\left(12x-64-32\right)=0\)
\(12x-96=0\)
\(12x=96\)
\(x=8\)
vay \(x=8\)
\(\left(12x-4\right)^3.8^3=4^{16}.16^3\)
\(\Leftrightarrow8\left(12x-4\right)^3=4^6.\left(4^2\right)^{^3}\)
\(\Leftrightarrow\left(96x-32\right)^3=4^6.4^6\)
\(\Leftrightarrow\left(96x-32\right)^3=16^6\)
\(\Leftrightarrow\left(96x-32\right)^3=\left(16^2\right)^{^3}\)
\(\Leftrightarrow\left(96x-32\right)^3=256^3\)
\(\Leftrightarrow96x-32=256\)
\(\Leftrightarrow x=\frac{256+32}{96}\)
Vậy \(x=3\)
(12x-4)3.83=43.163
<=> [(12x-4).8]3=(4.16)3
=> (12x-4).8=4.16
<=> 12x-4=8
<=> 12x=12
=> x=1
a/ 52x-3- 2. 52= 52. 3
52x-3- 2. 25= 25. 3
52x-3- 50= 75
52x-3= 75+ 50
52x-3= 125= 53
2x- 3= 3
2x= 3+ 3
2x= 6
x= 6: 2
x= 3
b/ (12x- 43). 83= 4. 84
12x- 64= (4. 84): 83
12x- 64= 4. 8= 32
12x= 32+ 64
12x= 96
x= 96: 12
x= 8
a <=>12x-4^3=32
<=>12x=96
<=>x=8
b, <=>3x-6=27
<=>3x=33
<=>x=11
c, <=>119-(x-6)=102
<=>x-6=17
<=>x=23
hok tot
a) ( 12x - 43 ) . 83 = 4.84
=> ( 12x - 43 ) : 4 = 84 : 83
=> ( 12x - 43 ) : 4 = 8
=> 12x - 43 = 8 . 4
=> 12x - 64 = 32
=> 12x = 96
=> x = 8
b) ( 3x - 6 ) . 3 = 34
=> ( 3x - 6 ) = 34 : 31
=> 3x - 6 = 33
=> 3x - 6 = 27
=> 3x = 33
=> x = 11
c) 2448 : [ 119 - ( x - 6 ) ] = 24
=> 119 - ( x - 6 ) = 102
=> x - 6 = 7
=> x = 13